Cytoplasmic region of beta-dystroglycan is essential for postsynaptic maturation and neuromuscular function in mice - Jeffrey M. Hord; Rolf Turk; Hajime Kusano; Erik P. Rader; Sarah Burns; Zeita Gastel; Sally J. Prouty; Liping Yu; Steven J. Burden; Kevin P. Campbell (Proceedings of the National Academy of Sciences, 2026)
The dystrophin–glycoprotein complex (DGC) provides structural integrity to the sarcolemma, and disruption of the DGC leads to muscular dystrophy. A core member of the DGC is dystroglycan (DG), which binds to extracellular ligands via α-DG and intracellular cytoskeleton via β-DG. Mutations in DAG1 or genes involved in the posttranslational processing of DG lead to a subset of neuromuscular diseases referred to as dystroglycanopathies. The importance of the α-DG extracellular interactions is well established; however, little is known about the significance of the β-DG intracellular interactions. Here, we investigate the importance of intracellular β-DG in neuromuscular health. Using a mouse that lacks a large intracellular region of β-DG (residues 777 to 893), we show that the deletion of cytoplasmic β-DG leads to skeletal muscle pathology accompanied by postsynaptic disruption. Our data show that within the specialized neuromuscular junction (NMJ), cytoplasmic β-DG is necessary for the localization of utrophin and rapsyn, and clustering of acetylcholine receptors. Moreover, we provide evidence that the postsynaptic abnormalities contribute to neuromuscular dysfunction in mice lacking the cytoplasmic region of β-DG. Further, using a mouse model that only lacks the C-terminal tail (residues 879 to 893) of β-DG, we demonstrate that skeletal muscle and NMJ health rely on β-DG residues 777 to 878. Together, our mouse models suggest that deletion of the cytodomain of β-DG surprisingly results in very severe neuromuscular pathophysiology in mice. Our results identify β-DG as a critical player in shaping and maintaining neuromuscular synapse architecture in vivo, thus further defining the molecular mechanisms underlying neuromuscular health.